Study of nano-hydroxyapatite/zirconia stabilized with yttria in bone healing: histopathological study in rabbit model - Abedi, Gholamreza; Jahanshahi, Amirali; Fathi, Mohamad Hosein; Haghdost, Iraj Sohrabi; Veshkini, Abas (Polish Journal of Pathology, 2014)
Acceleration of bone healing has always been a major challenge in orthopedic surgery, the aim of this study was an evaluation of the biological effects of zirconia-stabilized yttria on bone healing, using an in vivo model. Nano-hydroxyapatite powder with zirconia-stabilized yttria were inserted in rabbit tibia and then histologically analyzed and compared with non-treated controls so thirty six. New Zealand white male rabbits randomly divided into two groups of 18 rabbits each. A cortical hole of 4 mm diameter and 8 mm depth in each tibia was drilled. In group I, the defect was left empty, whereas in group II, the bone defect was packed with nano-hydroxyapatite/5% zirconia stabilized with yttria. Histological evaluations were performed at two, four and six weeks after the implantation. Microscopic changes on two groups along with the time course were scored and statistical analysis showed that the average scores in group II were significantly higher than the other groups (p < 0.05). Histological analysis was shown to be significantly improved by the nano-hydroxyapatite/5% zirconia stabilized with yttria compared with the control group, suggesting that this biomaterial promote the healing of cortical bone, presumably by acting as an osteoconductive.